Methods for overcoming seed dormancy in blue palm - de Oliveira Meireles, Rubens; Meireles, Vinicius Mendes; de Lima Sena, Welliton; da Costa, Brenda Oliveira; Júnior, Raimundo Nonato Colares Camargo; Pivetta, Kathia Fernandes Lopes [UNESP] (FapUNIFESP (SciELO), 2024)
The blue palm (Bismarckia nobilis) is one of the most used ornamental palms in landscaping, due to its size and slightly bluish fan-shaped leaves. However, its propagation is carried out through seeds and the germination of these seeds is extremely low, in addition to the plant growth being considered slow. This work aimed to compare the use of pre-germination treatments to break dormancy and accelerate germination of B. nobilis seeds. The effect of mechanical scarification (sanding the region opposite the embryonic axis), thermal (immersion in water at 40 ºC, 60 ºC and 80 ºC for 5 min) and chemical (immersion in sulfuric acid 98% for 15; 30; 45 and 60 min), as well as its imbibition in solutions containing GA3 (gibberellic acid) at concentrations of 250; 500; 750 and 1000 mg L-1 on germination and speed of germination of seeds of the species. The results showed that the pre-germination treatments of mechanical and thermal scarification presented the best results compared to the other treatments.
Métodos para superação da dormência de sementes da palmeira azul
Keywords: Bismarckia nobilis; escarificação mecânica; escarificação térmica; gibberellic acid; mechanical scarification; pre-germination treatments; thermal scarification; tratamentos pré-germinativos; ácido giberélico